Aminoadamantanes: from treatment of Parkinson's and Alzheimer's disease to symptom amelioration of long COVID-19 syndrome?. Issue 2 (1st February 2023) - Müller, Thomas; Riederer, Peter; Kuhn, Wilfried
ABSTRACT: Introduction: The aminoadamantanes amantadine and memantine are well known. They mainly act as N-methyl-D-aspartate antagonists. Areas covered: The antiviral drug amantadine moderately ameliorates impaired motor behavior in patients with Parkinson's disease. Memantine provides beneficial effects on memory function in patients with advanced Alzheimer's disease already treated with acetylcholine esterase inhibitors. Both compounds counteract impaired monoamine neurotransmission with associated symptoms, such as depression. They improve vigilance, lack of attention and concentration, fatigue syndromes according to clinical findings in patients with chronic neurodegenerative processes. Their extrasynaptic N-methyl-D-Aspartate receptor blockade weakens a prolonged influx of Ca 2+ ions as the main responsible components of neuronal excitotoxicity. This causes neuronal dying and associated functional deficits. Expert opinion: We suggest aminoadamantanes as future therapies for amelioration of short- and long-term consequences of a COVID 19 infection. Particularly the extended-release amantadine formulations will be suitable. They showed better clinical efficacy compared with the conventional available compounds. Amantadine may particularly be suitable for amelioration of fatigue or chronic exhaustion, memantine for improvement of cognitive deficits. Clinical research in patients, who are affected by the short- and long-term consequences of a COVID 19 infection, is warranted to confirm these still hypothetical putative beneficial effects of aminoadamantanes. Plain Language Summary: The drugs amantadine and memantine are known as aminoadamantanes. Amantadine improves motor skills in patients with Parkinson's disease. It also reduces fatigue in individuals suffering from multiple sclerosis. Memantine improves memory dysfunction linked to Alzheimer's disease. Aminoadamantanes affect communication between nerve cells by supporting neurotransmission of monoamines. Clinical studies have found that these drugs benefit patients with chronic neurodegenerative diseases, who have depression, fatigue, loss of attention or concentration deficits. These brain function problems may also appear to some extent due to COVID-19 infection. We suggest that aminoadamantanes could improve these problems in COVID-19 patients in both the short and long term. Clinical research is needed to confirm this hypothesis.